Impact of Geometry Dimension on Quality Factor and Mass-Sensitivity of PZT Thin Film-Based MicroCantilevers - Chi, Nguyen Thi Quynh; Minh, Nguyen Duc; Hung, Vu Ngoc (VNU Journal of Science: Mathematics - Physics, 2021)
The impact of the piezoelectric cantilever geometry and resonant mode on the quality factor and mass-sensitivity were investigated. The piezoelectric cantilevers with Pb(Zr 0.52 Ti 0.48 )O 3 (PZT) as an active layer were fabricated based on MEMS technology. The PZT thin films were grown on the silicon-on-insulator substrates by pulsed laser deposition. It is shown that the resonant frequency of a defined vibration mode is inversely proportional to the length squared of the piezoelectric cantilever. The experimental results indicated that a shorter cantilever length will contribute to a larger quality factor. The cantilever quality factor has values in a range of 190 to 505, depending on the length and resonant mode. The mass-sensitivity increases when the cantilever length decreases and reaches the highest value of 37.6 Hz/pg for the 100-µm-long cantilever. High-mode vibration was successfully exhibited for the higher mass-detection sensitivity.